The Obligations of the Iraqi Federal Supreme Court in Safeguarding the Constitution in Force - Handal Sharif, Maitham (Opción)
Observing statutes constitutionality aims primarily at safeguarding the constitutional texts. This helps to confront the legislations that involve conflicting with these texts in compliance with the principles of the supremacy of the constitution. The alteration of constitutional texts in Iraq brings up the issue of the scope of the jurisdiction of the Iraqi Federal Supreme Court (henceforth the IFSC, for short) in terms of its confined duty to the texts of the Iraqi Constitution that was enacted in 2005. The scope of observation of the constitutionality of laws may be extended to the texts of the abrogated Constitution of 1970.